The decision to germinate is regulated by divergent molecular networks in spores and seeds. Issue 3 (3rd June 2016) - Vesty, Eleanor F.; Saidi, Younousse; Moody, Laura A.; Holloway, Daniel; Whitbread, Amy; Needs, Sarah; Choudhary, Anushree; Burns, Bethany; McLeod, Daniel; Bradshaw, Susan J.; Bae, Hansol; King, Brian Christopher; et al.
Summary: Dispersal is a key step in land plant life cycles, usually via formation of spores or seeds. Regulation of spore‐ or seed‐germination allows control over the timing of transition from one generation to the next, enabling plant dispersal. A combination of environmental and genetic factors determines when seed germination occurs. Endogenous hormones mediate this decision in response to the environment. Less is known about how spore germination is controlled in earlier‐evolving nonseed plants. Here, we present an in‐depth analysis of the environmental and hormonal regulation of spore germination in the model bryophyte Physcomitrella patens ( Aphanoregma patens ). Our data suggest that the environmental signals regulating germination are conserved, but also that downstream hormone integration pathways mediating these responses in seeds were acquired after the evolution of the bryophyte lineage. Moreover, the role of abscisic acid and diterpenes (gibberellins) in germination assumed much greater importance as land plant evolution progressed. We conclude that the endogenous hormone signalling networks mediating germination in response to the environment may have evolved independently in spores and seeds. This paves the way for future research about how the mechanisms of plant dispersal on land evolved.